Wave propagation in micropolar monoclinic thermoelastic half space - Gupta, Rajani Rani (Zielona Góra: Uniwersytet Zielonogórski)
Propagation of waves in a micropolar monoclinic medium possessing hermoelastic properties based on the Lord- Shulman (L-S),Green and Lindsay (G-L) and Coupled thermoelasticty (C-T) theories is discussed. The investigation is divided into two sections, viz., plane strain and anti-plane strain problem. After developing the solution, the phase velocities and attenuation quality factor have been derived and computed numerically. The numerical results have been plotted graphically.
Keywords: micropolar; monoclinic; generalized thermoelastic